Ob padcu utopije - Decker, Pascal de (Urbani izziv, 2009)
Immediately after WW2 numerous large-scale housing estates began to spring up. More often than not they consisted of high-rises. Merely 50 years later a great number of these developments are in the process of demolition or are seriously undergoing restructuring. The Modernistic thoughts, inspired by the CIAM (Congres International d'Architecture Moderne) movement and Le Corbusier seem to have lost the appeal they once held. In this contribution we look into this evolution and more specifically, we focus on the misinterpretation ofthe importance of the (symbolic) meaning of housing by the Modernist movement. A misjudgement, that eventually resulted in the speedy dismantling of these estates.
Keywords: bivalna kultura; modernizem; prenova; stanovanjska arhitektura; stanovanjska naselja; večstanovanjske zgradbe